STRATEGI KOMUNIKASI PEMASARAN MEDICAL REPRESENTATIVE - Fredy Kurniadi; Didik Hariyanto (Kanal: Jurnal Ilmu Komunikasi, 2013)
Medical representative as the spearhead of the company that specialized in selling hard drugs and psychotropic substances should be able to market their products well and is consistent with the use of marketing communications strategy by personal medical representative. This study used qualitative methods with Medical representatives and specialized doctors as the informants using the analysis techniques of the domain of data and taxonomy. The result of the study is that representative medical marketing communications strategy can be systematically grouped into Opening (opening), Probing (questioning techniques), Supporting (presentation), Objection Handling (overcoming objections), and Closing (closing). To support it, the necessary thing is the ability of Productions knowledge. Other Medical representative strategy to support its activities are some programs such sponsorship Symposium, Seminar, Workshop, RTD (round table Discussion), customer service (service offers), entertainment and gimmick.